Utilization of wet brewers grains as a replacement for corn silage in lactating dairy cow diets - Mahnken, Christa Lynn (Kansas State University, 2010)
An evaluation of short-term replacement of corn silage (CS) and soybean meal with a blend of wet brewers grains (BG) and cracked corn on milk production and DMI was completed utilizing 8 primiparous (192 DIM) and 4 multiparous (191 DIM) mid-lactation Holstein cows. Milk production, composition, DMI, production efficiency, fatty acid composition and diet digestibility were evaluated. Cows were allotted to a 4 x 4 Latin Square with 3 replications blocked by parity, DIM and energy corrected milk (ECM). Crude protein and starch levels were balanced between diets by varying the levels of cracked corn and soybean meal in four diets; 0 BG (0% wet BG and 24% CS of diet DM), 12 BG (12% wet BG and 12% CS), 18 BG (18% wet BG and 6% CS), and 24 BG (24% wet BG and 0% CS). Fifteen day periods were used, d11-15 designated for collection. Orts were collected daily and TMRs were fed at 5 to 10% of previous day’s intake. Cows were milked 3x/day and individual milk weights recorded at every milking. Milk samples, body weights and BCS were taken -2 and -1d pre-trial to obtain baseline data and d14 and 15 of each period. During collection, samples of TMR and orts were taken d1, 3 and 5. Fecal grab samples were taken d12-15 at 8 hr intervals and advanced 2 hrs every 24 hr period to account for diurnal variation. Dry matter intake was similar (P=0.33) among treatments (20.3, 20.8, 20.9 and 21.2 kg/cow) for 0 BG, 12 BG, 18 BG AND 24 BG respectively, however CP intake of 24 BG tended to be greater (P=0.05) than 0 BG. NDF intake was lower for 0 BG compared to all other treatments and 24 BG was higher than 12 BG (P=0.0007). Dietary fat intake was different (P<0.001) across all treatments, increasing with greater BG inclusion. Inclusion of BG had no effect (P=0.37) on milk production (30.5, 31.5, 31.6 and 32.1 kg/cow), fat percent or amount, protein percent, SNF, lactose or SCC, but protein yield (P=0.04) was lower and MUN (P=0.05)tended to be lower with 0 BG compared to 18 BG and 24 BG. Efficiency of milk production did not differ (P=0.93) among treatments. Milk fatty acid profiles were different among treatments, with general increases of individual fatty acids as BG inclusion increased. No differences were found in DM, CP or ADF digestibility across treatments. Results suggest wet BG fed simultaneously with grass hay can be utilized as a short-term replacement for CS in mid-lactation dairy cow diets.
Keywords: Brewers grains; By-product feeds; Dairy cattle; Agriculture, Animal Culture and Nutrition (0475)